Pengaruh Pengelolaan Kelas Dan Minat Belajar TerhadapPrestasi Belajar Siswa Mata Pelajaran Ipa Kelas IvSD Muhammadiyah 23 SurakartaTahun Ajaran 2015/2016 - Pratiwi Wulandari, Dwi, Drs Suwarno, SH.,M.Pd (2016)
This study aims to determine: (1) the effect of classroom management on student learning outcomes science subjects fourth grade SD Muhammadiyah 23 Surakarta academic year 2015/2016, (2) the effect of interest in learning the results of student learning science subjects fourth grade SD Muhammadiyah 23 Surakarta the academic year 2015/2016, (3) the effect of classroom management and interest in learning the results of student learning science subjects fourth grade SD Muhammadiyah 23 Surakarta academic year 2015/2016. This research is a quantitative research. The place of research in SD Muhammadiyah 23 Surakarta. The study population was the fourth grade students of SD Muhammadiyah Surakarta Academic Year 2015/2016 23 totaling 62 students, how sampling using sampling nonprobability with the kind of systematic sampling totaling 31 students.The technique of collecting data using questionnaires and documentation. The results showed that: (1) there is the influence of classroom management on student learning outcomes science subjects fourth grade SD Muhammadiyah 23 Surakarta academic year 2015/2016, which is indicated by the value prob.t (0,004) is less than 0.10; (2) there are significant interest in learning the results of student learning science subjects fourth grade SD Muhammadiyah 23 Surakarta of the school year 2015/2016, which is indicated by the value prob.t (0.056) is less than 0.10; (3) there is the influence of classroom management and interest in learning the results of student learning science subjects fourth grade SD Muhammadiyah Surakarta academic year 2015/2016, with the regression equation Ý = -26,346+ 0,722X1 + 0,546X2, where the value Prob.Fstat < 0 , 10 (0.000 <0.10). Keywords: Classroom Management, Interest in Learning, Learning achievement